A Study of Post M.B.B.S. Life Perceptions Among Recently Graduating Doctors in Surat City - Kanan T. Desai; Vinesh Shah; Danish B Kanpurwala; Ravi A Jariwala; RK Bansal (Medsci Publications, 2012)
Background: In today's time, insurmountable uncertainties in the medical field leads to lot of frustrations amongst the new pass out medical graduates. Aim: The current study was planned with an aim to explore the perceptions of the recent medical graduates/graduating students on life after M.B.B.S. Methods: This is a cross-sectional study comprising of face-to-face interviews using a semi-structured interview schedule among 400 simple randomly selected recently graduated/graduating M.B.B.S. doctors of Surat Municipal Institute of Medical Education and Research. Results: Majority 70% of respondents were satisfied with their decision of taking admission in M.B.B.S. with satisfaction level higher amongst females compared to males (P=0.002). As compared to interns, higher satisfaction rate was observed among residents (P=0.042) and senior students (P=0.008). Conclusion: Freshly graduating doctors face a very perplexing situation after M.B.B.S, as after years of studies, the brightest students, face an uncertain future.